Uji kualitas air pengolahan IPAM Karangpilang III berdasarkan parameter mikrobiologi di lab Karangpilang perusahaan daerah air minum (PDAM) Surya Sembada Kota Surabaya - Martini, Vindi Almas (Maliki Interdisciplinary Journal, 2023)
The good quality of drinking water is assessed from microbiological parameters, namely not having a total amount of Coliform and fecal Coliform of 0 per 100 ml of water. The purpose of this study was to monitor the water quality of Karangpilang III IPAM treatment by isolating and identifying coliform bacteria in the processing water of Karangpilang III IPAM at PDAM Surya Sembada, Surabaya. The research method in this study is descriptive with an observational approach. This research was carried out during the Field Work Practice (PKL) from July to June at the Surya Sembada Regional Drinking Water Company (PDAM) Laboratory, Surabaya City. Research on water quality with microbiological parameters using the Most Probable Number (MPN) method involved two stages, namely a prediction test using Lactose Broth (LB) media and a confirmation test using Brillian Green Lactose Broth (BGLB) and EC Broth media. The results showed that the microbiological quality of Karangpilang III processing water met the SNI 01-0220-1987 standards and also complied with the standards of the Minister of Health of the Republic of Indonesia No. 32 of 2017.